Strategies for Influencers to Enhance Consumer Loyalty in Virtual Marketplaces - Firmansyah, Firmansyah (Journal of Social Commerce, 2023)
The following research aims at examining the ways of engaging influencers in the context of consumer loyalty in virtual marketplaces. Thus, being the quantitative study, the research investigates the impact of content quality, the post frequency, the time spent for the interaction with the followers, and the cooperation with brands for consumer loyalty. Through the analysis of the research information, it is clear that content quality and level of engagement with followers, are negatively related with CL. Their quality creates trust while engaging with followers strengthens a personal bond. These two, however, have a positive correlation with the client’s loyalty, but this correlation is controlled by the other variables. The research adds to the existing body of literature by offering quantitative analysis of the comparative magnitude of these strategies and stressing on the cross sectional relevance of their effects. The findings hereby presented provide practical suggestions that would help the influencers & marketers to enhance & sustain the consumer relationships in the context of the dynamic social media environment.